Comparability of Mean Scores of Gifted Students on the Jordanian Version of the Overexcitability Questionnaire (OEQII) Across Gender - Abdelhafez Q. Al-Shayeb (Sultan Qaboos University, 2016)
The aim of the present study was to investigate the comparability of the mean scores of gifted students on the Jordanian version of the Overexcitabilities Questionnaire OEQII in light of gender. A cluster random sampling technique was used to collect data from 448 males and females gifted students who are enrolled in the King Abdullah II Schools of Excellence in Jordan. Results of multi-group confirmatory factor analysis clearly indicate that measurement invariance with respect to gender is untenable. Uniform measurement bias was observed in all subscales. Results suggested that the Jordanian version of OEQII failed to display scalar invariance across gender which is a requirement to scores' comparability. Initial analyses of fitting the model to the data for each subscale suggested that the theoretical common factor structure didn't display a reasonable fit to the data for any subscale. Results suggested that the Jordanian version of OEQII failed initially to display configural invariance across gender. In light of the results, it is recommended that the mean-level comparisons of OEQII subscale scores across gender should be interpreted with caution. Moreover, re-validating and re- standardizing of the Jordanian version of OEQII was suggested to justify mean scores comparability on its subscales.